Motor Vibration and Temperature Detector by Using IoT - Arman Sabri, Amirah Syafiqah; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2025)
The project includes the description and deployment of a real-time Motor Vibration and Temperature Detector based on Internet of Things (IoT) technology which is designed to prevent sudden motor failure and preventive maintenance. This system is implemented by the use of ESP32 microcontroller in combination with temperature sensors, DS18B20 and vibration sensor, ADXL335. Critical thresholds were set at 55°C for temperature and 0.5G for vibration based on NEMA and ISO 10816 standards. In an experimental test, the system was able to warn over hazardous conditions that occurred when the vibration was above 0.5G and temperature was above 38.0°C at 2541. 6 RPM. The results indicated that the parameters did not pose any danger at low speeds which at 0. 01G and 36.1 C when 100. 35 RPM but only became "Hazard" when speed was increased. This information was shown on a local 20x4 LCD display as well as through the Blynk service and buzzer initiated in case of critical events. The system was found to have a 100% achievable level in detecting abnormal conditions to predetermined thresholds and have the possibility of saving time to be incurred in event of downtimes since it has the ability to warn of the onset of those abnormalities. This type of solution based on the IoT allows the company to introduce a cost effective, scalable monitoring of the condition of the motors, contributing to the transformation of the maintenance strategies in industry turning reactive maintenance to predictive.